2021
DOI: 10.1029/2021gl092876
|View full text |Cite
|
Sign up to set email alerts
|

Large Circulation Patterns Strongly Modulate Long‐Term Variability of Arctic Black Carbon Levels and Areas of Origin

Abstract: Black Carbon (BC) aerosol is a major climate forcer in the Arctic. Here, we present 15 years (2001–2015) of surface observations of the aerosol absorption coefficient babs (corresponding to Equivalent BC), obtained at the Zeppelin Observatory, Ny Ålesund, Svalbard, coupled with backward transport modeling with Flexpart in order to calculate the Potential Source Contribution Function (PSCF) for BC. The observed long‐term variability superimposed on a strong annual cycle is studied as a function of large‐scale c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 65 publications
5
10
0
Order By: Relevance
“…The Eurasian continent has been shown to be one of the most important contributors to BC measured at ZEP (see Fig. S9); a finding which is in agreement with multiple other studies (Hirdman et al, 2010;Backman et al, 2014;Stathopoulos et al, 2021). The fact that this region contributes most to observations of σ ap is the result of a combination of source strength, transportation, and removal processes.…”
Section: Biomass Burning Eventssupporting
confidence: 89%
See 3 more Smart Citations
“…The Eurasian continent has been shown to be one of the most important contributors to BC measured at ZEP (see Fig. S9); a finding which is in agreement with multiple other studies (Hirdman et al, 2010;Backman et al, 2014;Stathopoulos et al, 2021). The fact that this region contributes most to observations of σ ap is the result of a combination of source strength, transportation, and removal processes.…”
Section: Biomass Burning Eventssupporting
confidence: 89%
“…Previous studies have suggested that this increase in the contribution of more marine air masses is likely the result of changes in air circulation patterns (Heslin-Rees et al, 2020). The phase of the Scandinavian pattern, a large-scale circulation pattern, was shown to affect the variability in transported BC (Stathopoulos et al, 2021); during the cold period, higher concentrations of BC were present when sources were limited to more northern regions, as opposed to when source regions extended further south, and experienced more wet removal.…”
Section: Biomass Burning Eventsmentioning
confidence: 91%
See 2 more Smart Citations
“…The eBC mass concentrations are higher in the winter months compared to the summer months, reflecting the expected annual cycle of this species at the measurement site. , The annual mean of eBC (18.9 ± 35.0 ng m –3 ) is lower than the reported average of long-term observations (average 39 ng m –3 , median 27 ng m –3 ) at the observatory from 1998 to 2007 . The lower eBC mass concentrations in 2020 compared to the period 1998–2007 agree with the reported decreasing trend of eBC at the Zeppelin Observatory .…”
Section: Resultssupporting
confidence: 72%